Resource redeployment and corporate strategy - Folta, Timothy B.; Helfat, Constance E.; Karim, Samina; Silverman, Brian S. (Advances in strategic management ;, 2016)
It has been long understood that value creation by corporate strategists is determined by their ability to effectively deploy resources across multiple business units. Recently, scholarly attention has been dominated by studies of "synergy", or sharing resources across businesses. However, a second type of resource deployment, "resource redeployability" or "resource configuration", where resources are withdrawn from one business unit and reallocated to another may not only effect firm value creation, but also firm and industry evolution. This volume advances the resource deployment and synergy debate, and how they differentially affect value and firm decision-making. It clarifies the theoretical determinants and effects of each, revisiting prior work that investigates the benefits of synergy-based strategy, and assessing the benefits of an increased focus on redeployability.